SOCIAL-ENVIRONMENTAL PROBLEMS AND THE POLITICAL DIMENSION OF SPACE - Orsi, Rafael Alves [UNESP] (Univ Federal Fluminense, 2016)
Social-environmental issues have gained notoriety in the last decades. There is a growing concern in some aspects and on different scales, mainly in regard to global climate change and its results, not only related to the dynamics of nature, but even relating to the changes that they can bring to economic, social and political relations, on multiples scales - global, regional and local. Considering the local as the scale of daily life, it is at this level that people realize and feel the main problems that affect them. Thus, as a reactive action, they can engender local and even global transformations. From this local-global aspect, we want to discuss in this paper some points about the political dimension on different spatial scales and civil societies organized involvement toward mitigate problems in their daily sphere, even when the origins of these disturbances are global and extrapolate to their territorial limits.
Keywords: Social-Environmental Problems; Spatial Scales; Political Relations